THE EFFECT OF COMBINATION OF NUMBER HEAD TOGETHER AND TWO STAY TWO STRAY LEARNING MODELS ON MATHEMATICAL LEARNING OUTCOMES AND ACTIVENESS OF SENIOR HIGH SCHOOL STUDENTS - Andi Kaharuddin; Nining Hajeniati (International Journal of Educational Best Practices, 2020)
An engaging learning process will affect learning outcomes and student activeness during the learning process. The present study was conducted to investigate the effect of the combinatory use of Number Head Together and Two Stay Two Stray learning models on the scores of high school students’ mathematical tests and learning activeness. It was an experimental-based study with One Group Pre-test Post-test design. The population of this study was all high school students in Kendari, with Cluster Random Sampling as the method to choose the sample. Final test and observation were used as instruments to collect data. The data were analyzed using descriptive and inferential statistics with the One-Sample t-test. Results showed that (1) the combinatory use of both learning models improved learning outcome by increasing students’ average test scores from an average score of 68 (pre-test) to an average of 83 (post-test) with a gain value of 0.71; (2) the learning models had a positive influence on student activeness during the learning process, proven by a score of 3.3 (positive category). It was also evidenced by the results of the t-test showing that the t-count score was greater than the t-table. Therefore, the combinatory use of Number Head Together and Two Stay Two Stray learning models has a significant effect on increasing the learning outcome and learning activeness of high school students in the mathematic class.